Good Sam Campground guide. (Good Sam Guide Series., 2022)
"The Good Sam Campground Guide is your indispensable travel resource of RV parks and campgrounds in North America, including Good Sam Parks. Good Sam's exclusive RV park rating will help you decide where to stay. The comprehensive volume features information about 12,300 private RV parks, public campgrounds, and services, including 2,000 Good Sam Parks. Use the Good Sam Campground & Coupon Guide as a gateway to RV adventure. This valuable book includes expanded travel articles, special coupon savings, detailed state and provincial maps."--